A Revolutionary Model to Improve Science Education, Teachers, and Scientists - Brawley, Susan; Pusey, Judith; Cole, Barbara; Gott, Lauree; Norton, Stephen (Maine Policy Review, 2008)
To meet many modern global challenges, we need to promote scientific and technical literacy. The U.S. National Science Foundation (NSF) supports a “revolutionary” program to connect science education at all levels, from elementary through graduate school. The authors demonstrate how Maine has benefited from this program. They describe the University of Maine’s NSF-funded “GK-12 STEM” program, which placed graduate and advanced undergraduate science and technology students in elementary, middle, and high school classrooms; provided equipment for the schools; and offered training and professional development for the partner teachers. The authors urge the state, universities, and school districts to continue to use this model to increase science literacy and research capacity.